Exposure of a population of invasive wild pigs to simulated toxic bait containing biomarker: implications for population reduction. Issue 4 (19th November 2018) - Snow, Nathan P; Lavelle, Michael J; Halseth, Joseph M; Glow, Michael P; VanNatta, Eric H; Davis, Amy J; Pepin, Kim M; Tabor, Rustin T; Leland, Bruce R; Staples, Linton D; VerCauteren, Kurt C
Abstract: BACKGROUND: An international effort to develop an acute and humane toxic bait for invasive wild pigs ( Sus scrofa ) is underway to curtail their expansion. We evaluated the ability to expose a population of wild pigs to a simulated toxic bait (i.e., placebo bait containing a biomarker, rhodamine B, in lieu of the toxic ingredient) to gain insight on potential population reduction. We used 28 GPS‐collars and sampled 428 wild pigs to examine their vibrissae for evidence of consuming the bait. RESULTS: We estimated that 91% of wild pigs within 0.75 km of bait sites (total area = 16.8 km 2 ) consumed the simulated toxic bait, exposing them to possible lethal effects. Bait sites spaced 0.75–1.5 km apart achieved optimal delivery of the bait, but wild pigs ranging ≥ 3 km away were susceptible. Use of wild pig‐specific bait stations resulted in no non‐target species directly accessing the bait. CONCLUSION: Results demonstrate the potential for exposing a large proportion of wild pigs to a toxic bait in similar ecosystems. Toxic baits may be an effective tool for reducing wild pig populations especially if used as part of an integrated pest management strategy. Investigation of risks associated with a field‐deployment of the toxic bait is needed. © 2018 Society of Chemical Industry Abstract : A new toxic bait is under development to curtail invasive wild pigs in the USA and Australia. Proper baiting strategy can expose most wild pigs in a large population to this bait.